Сакральний мультиверс поетичних творів Василя Барки - Маланій, Олена; Malaniy, Olena (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті йдеться про складний і неоднозначний світ українського письмен- ника діаспори Василя Барки, про його надзвичайно глибоку філософську систему світобудови, про сакральний всесвіт його поезій, про сковородинське начало його світовідчуття. Автор намагається відшукати відповіді на неоднозначні питання релігійності письменника, з’ясувати витоки, впливи і пошуки себе у світі, основи християнського та мистецького осягнення навколишнього світу.The article deals with the complex and ambiguous world of the Ukrainian diaspora writer Vasyl Barka, on his very deep philosophical system of the universe, about the sacred universe of his poems about Skovorodinsky beginning of his attitude, about enlightenment and visions that influenced the life and artistic landmarks of the writer. The author tries to find answers to ambiguous questions religion writer to find out the origins of his distinctive creative influences and searches itself in the world, recognize the basics of the Christian and artistic understanding of the surrounding, to trace the emergence of the idea of God in the creative lifetime of the poet.
Sacred Multiverse of Poetry Vasyl Barka
Keywords: сакральний світ; релігійний простір; мультиверс; філософія; мікро- і макрокосм; поезія Василя Барки; sacred world; religious space; multiverse; philosophy; micro- and macrocosm; poetry Vasyl Barka